Cover Image. (11th March 2018) - Uchida, Y.; Terada, K.; Madokoro, Y.; Fujioka, T.; Mizuno, M.; Toyoda, T.; Kato, D.; Matsukawa, N.
Abstract : The cover image, by Yuto Uchida et al., is based on the Clinical Commentary Stiripentol for the treatment of super‐refractory status epilepticus with cross‐sensitivity, DOI:10.1111/ane.12888 .